A novel meaningful secret image sharing method based on Arabic letters - Derya Avci (Kuwait Journal of Science)
In recent years, the providing of information security for multimedia has become an important subject of study. Visual cryptography and secret sharing is protected image contents without using complex mathematically operators. Thus, visual cryptography and secret sharing are widely used. In this paper, Letter based Secret Image Sharing (LSIS) for protecting of image contents. For this purpose, secret sharing and data hiding algorithms are used together in this LSIS method. The LSIS method consists of two parts. These are generating of meaningful secret sharing and data hiding. Secret sharing and visual cryptography methods commonly generate noise-like images. The noise-like images have attracted the attention of the attackers and several attacks have been developed to break these encrypted images. To prevent these attacks, meaningful secret shares are generated and these secret shares are embedded into cover image. In this paper, we proposed a novel secret image sharing method based on Arabic letters. The proposed method is used Arabic letters for generating meaningful secret shares and data hiding functions are used for camouflage. RGB images are used for cover images. In proposed method, secret shares are embedded into R, G and B channels respectively. Thus, cheatings  occurred in visual cryptography are prevented.